On the characteristics of structural dispersive wave solutions for the Fokas model - Hadil Alhazmi; E. K. El-Shewy; Mahmoud A. E. Abdelrahman (AIP Advances)
In this paper, we use the unified solver technique to investigate the effective irregular wave propagations in dispersive and dissipative modes via the (2 + 1)-dimensional Fokas model, which describe a simple extension of the nonlinear Schrödinger equation. Using a complex traveling wave transformation, the Fokas model is transformed into a nonlinear ordinary differential equation. The unified solver method subsequently produces several kinds of solitary wave solutions. More precisely, it provides solutions in trigonometric, hyperbolic, dissipative, rational, solitonic, and super soliton forms. Among the many benefits of the given technique are the reduction of complex computations and the concise presentation of important results. To demonstrate the wave structures for the dispersive and dissipative Fokas model, two-dimensional, three-dimensional, and contour plots of selected solutions are created utilizing the MATLAB software. We also demonstrate how physical parameters affect the acquired solutions’ behavior. The suggested method could be improved to address more complex applied science problems.